Cross-laminated timber and glulam from low-density paraserianthes falcataria: a look into densification and shear strength - Liew, Kang Chiang; Tan, Yu Feng; Charles Michael Albert; Vinodini Raman (MDPI, 2022)
The aim of this study was to investigate the shear performance of cross-laminated timber (CLT) and glulam made from densified Paraserianthes falcataria laminas. The densification process involved pre-treatment, compression with heat (105 ◦C, 6 MPa), and a cooling phase. CLT was manufactured from densified laminas of different thicknesses (24–60 mm), while glulam was produced from densified laminas that underwent pre-treatments of (1) pre-steaming (0–30 min) and (2) alkaline pre-treatment (sodium hydroxide (NaOH) concentrations: 0%–9%). Both CLT and glulam were cut into a pre-determined size before being subjected to a block shear test. The findings showed that the presence of pre-steaming (20 min) exhibited the highest shearing strength value. In contrast, alkaline pre-treatment reduced the shear performance of glulam. Here, 24 mm and 30 mm CLT were found to have the highest shearing strength among the parameters. Pre-steamed laminas showed better wettability, but no statistically significant correlation between the contact angle and shear strength of glulam. The densification process reduced the fiber pore areas of the laminas. The fiber pore areas with a shear strength of glulam, with or without alkaline pre-treatment, revealed a weak correlation. The correlation between fiber pore areas and the shear strength of CLT show no statistical significance. Here, 30 mm CLT with lowest moisture content and highest wood failure percentage exhibited a better bonding performance.